2016
DOI: 10.1002/bsl.2249
|View full text |Cite
|
Sign up to set email alerts
|

Stress, stress‐induced cortisol responses, and eyewitness identification performance

Abstract: In the eyewitness identification literature, stress and arousal at the time of encoding are considered to adversely influence identification performance. This assumption is in contrast with findings from the neurobiology field of learning and memory, showing that stress and stress hormones are critically involved in forming enduring memories. This discrepancy may be related to methodological differences between the two fields of research, such as the tendency for immediate testing or the use of very short (1–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(77 citation statements)
references
References 44 publications
8
67
1
1
Order By: Relevance
“…One week later, participants returned for a second session to identify the confederate in a lineup. The eyewitness identification results are unrelated to our research question and reported elsewhere (see Sauerland et al, 2015).…”
Section: Sai Recall Performance Under Stress 11supporting
confidence: 53%
“…One week later, participants returned for a second session to identify the confederate in a lineup. The eyewitness identification results are unrelated to our research question and reported elsewhere (see Sauerland et al, 2015).…”
Section: Sai Recall Performance Under Stress 11supporting
confidence: 53%
“…Only significant comparisons are reported. The referring statistics will not be reported in the text, but can be found in Tables 3-5. Two ways of handling don't-know responses were possible: treating them as missing values or coding them as lineup rejections (see Sauerland et al, 2016, for a similar approach). We conducted both analyses, and this resulted in analogous outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…This was based on research showing that VR can be used to create high degree of realness and believable events [18]. Moreover, due to questions concerning underestimated effects from laboratory-based 2D studies [4] and the suggestion that a 2D method might not be a suitable for investigating effects of stress on eyewitness accuracy [16], we were interested in creating a proof of concept design that would be more comparable with a real life setting.…”
Section: Discussionmentioning
confidence: 99%
“…The implications are that 2D video is lacking in both realness and immersion and this means that 2D video fails to elicit emotional reactions that are comparable to real life, which in turn leads to small effects. Sauerland and colleagues [16] also state that very few eyewitness studies (in contrast to neurological studies) have investigated stress with objective measures, relying instead on subjective assessments. This further complicates the comparison between 2D and real life, leaving a gap in the field that has not been sufficiently investigated.…”
Section: Practical Implications and Future Researchmentioning
confidence: 99%
See 1 more Smart Citation